Influence of friction in the armored face conveyor chain on dynamics and energy efficiency - Osichev, Alexander; Tkachenko, Andrii (Національний технічний університет "Харківський політехнічний інститут", 2021)
The range of values of the coefficient of resistance to movement of the chain of typical longwall armored face conveyors and the coefficient of inner viscous friction in the chain, both immersed in the moving load and during the idle run of the conveyor, is estimated. The computer model of the conveyor is built as a multi-mass elastic-viscous stretched closed chain without sag with the number of masses n = 200 and one induction drive motor located in the head of the conveyor. Using the constructed model, three-dimensional space-time dynamic characteristics of speeds and forces in the chain of the CP72 longwall armored face conveyor are obtained. Start up to rated speed v≈1 m / s and the working process is simulated with an unloaded conveyor. The spatial form of frictional self-oscillations in the model with distributed parameters is shown. The resonance frequencies and amplitudes of oscillations of the efforts in the circuit and the length of the corresponding spatial waves have been determined. It was found that at the first and second resonance frequencies, self-oscillations are not excited, since the damping effect of the electric drive is quite pronounced in this frequency band. The direct connection of vibration amplitudes with the energy efficiency of the conveyor electric drive is indicated.

Оцінений діапазон значень коефіцієнта опору переміщенню ланцюга скребкових конвеєрів і коефіцієнта внутрішнього в'язкого тертя. Отримано тривимірні просторово-часові динамічні характеристики швидкостей і зусиль в ланцюзі скребкового конвеєра СР72. Показана просторова форма фрикційних автоколивань в моделі з розподіленими параметрами. Зазначено на прямий зв'язок амплітуд коливань з енергоефективністю електроприводу конвеєра.
Вплив тертя в ланцюзі скребкового конвеєра на його динаміку і енергоефективність
Keywords: armored face conveyor; internal viscous friction; coefficient of resistance to movement; frictional self-oscillations; model; dynamic characteristics; forces in the chain; 3D-graphs; скребковий конвеєр; внутрішнє в'язке тертя; коефіцієнт опору переміщенню; фрикційні автоколивання; модель; динамічні характеристики; зусилля в ланцюзі; 3D-графіки